6.3k views
3 votes
(ab^2 x -b^4a^3)^2

What is the answers

User YYC
by
4.7k points

1 Answer

5 votes

Answer:


\left(ab^2x-b^4a^3\right)^2:\quad a^2b^4x^2-2a^4b^6x+a^6b^8

Explanation:

Given the expression


\left(ab^2\:x\:-b^4a^3\right)^2

solving the expression


\left(ab^2\:x\:-b^4a^3\right)^2


\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \left(a-b\right)^2=a^2-2ab+b^2


a=ab^2x,\:\:b=b^4a^3

so the expression becomes


=\left(ab^2x\right)^2-2ab^2xb^4a^3+\left(b^4a^3\right)^2


=a^2b^4x^2-2a^4b^6x+a^6b^8

Thus,


\left(ab^2x-b^4a^3\right)^2:\quad a^2b^4x^2-2a^4b^6x+a^6b^8

User Parisa
by
5.3k points